Evaluation of social appearance anxiety in patients with acne vulgaris - Afzal, Umaima; Hafeez , Javeria; Naheed, Aqsa; Naveed, Tehseen; Sundus, Madhia; Anjum, Muhammad (Journal of Pakistan Association of Dermatologists, 2023)
Objective This study aims to calculate the mean social anxiety score among individuals with acne vulgaris. Â Methods This Descriptive, cross-sectional study was done in Dermatology Department, P.A.E.C General Hospital Islamabad from 15th July 2021 to 14th January 2022. The data included 704 individuals with moderate to severe acne, ranging from eighteen to thirty-five years of age. Chronic renal failure, chronic liver disease and polycystic ovarian syndrome were excluded. Written-inform content was taken from participants. Data was collected by proforma prepared specifically for this research including all demographics (age, gender, residency, and education). Â Results The study’s participants ranged in age from 18 to 35, with a mean age of 26.24 and 3.88 years. The average age of the 324 patients (46.02%) was between 18 and 35. In our investigation, we discovered that acne vulgaris patients had a mean social appearance anxiety score of 34.36Â±7.56. Â Conclusion According to the study’s findings, psychotherapy treatments can be used to enhance the quality of life while lowering morbidity by appropriately assessing social appearance anxiety levels in these specific patients. Â